False Belief Development in Children Who Are Hard of Hearing Compared With Peers With Normal Hearing - Walker, Elizabeth A. (J Speech Lang Hear Res, 2017)
PURPOSE: This study investigates false belief (FB) understanding in children who are hard of hearing (CHH) compared with children with normal hearing (CNH) at ages 5 and 6 years and at 2nd grade. Research with this population has theoretical significance, given that the early auditory–linguistic experiences of CHH are less restricted compared with children who are deaf but not as complete as those of CNH. METHOD: Participants included CHH and CNH who had completed FB tasks as part of a larger multicenter, longitudinal study on outcomes of children with mild-to-severe hearing loss. Both cross-sectional and longitudinal data were analyzed. RESULTS: At age 5 years, CHH demonstrated significant delays in FB understanding relative to CNH. Both hearing status and spoken-language abilities contributed to FB performance in 5-year-olds. A subgroup of CHH showed protracted delays at 6 years, suggesting that some CHH are at risk for longer term delays in FB understanding. By 2nd grade, performance on 1st- and 2nd-order FBs did not differ between CHH and CNH. CONCLUSIONS: Preschool-age CHH are at risk for delays in understanding others' beliefs, which has consequences for their social interactions and pragmatic communication. Research related to FB in children with hearing loss has the potential to inform our understanding of mechanisms that support social–cognitive development, including the roles of language and conversational access.